Roman bronze helmets from the Republican period and the Early Principate in Slovenia - Istenič, Janka (Arheološki vestnik, 2018)
Archaeological sites in Slovenia have yielded a number of Roman bronze helmets from the Late Republican and Early Imperial periods. More precisely, there are six (nearly) complete examples, several fragments of another helmet, five pieces of five different other helmets and possibly a cheek-piece. Four of the helmets belong to the Etrusco-Italic type, with the bowl and knob made in a single piece and with a polished exterior, of which the latest dated example is from around 70 BC. The other helmets or their parts are of the Buggenum (upper part of one helmet with a crest-knob) and Haguenau types (two helmets, two crest-knobs, two upper part fragments with a crest-knob), one also of the transitory form between the two types; all these date to the Early Principate. The helmets have been subjected to PIXE analyses to determine the approximate elemental composition. The results have shown that the helmets proper are mainly made of bronze with a medium amount of tin (roughly 6 to 12%) and no or very little lead or other elements, the hinges for attaching the cheek-pieces are of bronze and on one helmet of iron, rivets are of copper and on one helmet of iron, while the use of brass and the practice of soldering have been recorded on the helmets of the latest type (Haguenau) and on the helmet of the transitory Buggenum/Haguenau form.